Beyond the Liver: Exploring Gut Microbiota Driven Drug Metabolism and Personalized Therapeutics - Yadav, Satyam; Singh, Gursimran; Aran, Khadga Raj (The International Journal of Gastroenterology and Hepatology Diseases, 2025)
The Gut Microbiota (GM) is gaining recognition for its important role in drug metabolism, significantly impacting the bioavailability, therapeutic efficacy, and toxicity of drugs. We describe how enzymes from gut microbes influence drug bioavailability, therapeutic outcomes, and possible adverse reactions, which contribute to considerable individual differences in drug responses. According to microbiome studies, including metagenomic sequencing, cutting-edge in vitro models, and bioinformatics approaches, intricate interactions between the microbiota and drugs are being revealed, paving the way for personalized therapeutic strategies. Additionally, this review describes therapeutic approaches aimed at altering GM composition, such as probiotics, prebiotics, and fecal microbiota transplantation, to enhance the effectiveness of drugs and reduce the risk of toxicity. Beyond scientific findings, we also focus on the regulatory and clinical implications, emphasizing the need for a structured framework that integrates microbiota-related considerations into drug development and treatment. As pharmacomicrobiomics advances, incorporating microbiome profiling into clinical practice holds promise for enhancing the efficacy and safety of drug treatments. Ultimately, this review seeks to deepen understanding of the GM’s influence on drug metabolism, supporting a transition towards microbiome-informed precision medicine and promoting tailored, safer healthcare solutions that meet the needs of diverse patient populations as well as gut microbiome's structure, composition, and dynamic roles which emphasizes its enzymatic diversity and metabolic pathways that aid in drug transformation and affect pharmacokinetics in conjunction with traditional liver functions.
Keywords: microbiome-drug interactions